Harmonization Of Fajr Time In Indonesia: The Strategic Role Of Mui Fatwa In Uniting Different Views - Alamsyah; Lomba Sultan; Mualimin Mochammad Sahid; Abdul Halim Talli (Universitas Islam Negeri Mataram, 2026)
Variations in determining the beginning of Fajr time in Indonesia, especially the difference between the -18° and -20° solar depression criteria, have sparked debate among Muslim communities. Nahdlatul Ulama, Muhammadiyah, and Wahdah Islamiyah apply different criteria based on fiqh reasoning, astronomical calculation, and observational interpretation of fajr ṣādiq. This condition often confuses the public and may weaken communal unity, particularly when different prayer schedules circulate without a shared explanatory framework. This study examines the strategic role of the Indonesian Ulema Council (MUI) fatwa as an integrative instrument for harmonizing differences in determining Fajr prayer time. Using a literature study method, the research integrates bayani, burhani, and irfani approaches and analyzes relevant documents and fatwas qualitatively. The bayani approach examines Islamic legal arguments, the burhani approach analyzes astronomical criteria and observational differences, while the irfani approach explains ethical and spiritual considerations in maintaining communal harmony. The findings show that an MUI fatwa can function as a harmonizing mechanism if supported by transparent astronomical evidence and inclusive fiqh reasoning. Such a fatwa can strengthen Islamic legal credibility, reduce public confusion, and reinforce ukhuwah Islamiyah through synergy between science and sharia for contemporary Indonesian Muslims facing diverse institutional prayer-time standards today in practice.